Study On Work Related Factors of Agate Grinders in Shakarpura Khambhat, Gujarat - Sharma, Deepak B; Patel, Tushar A (National Journal of Community Medicine, 2011)
Decorative carving of agate stone is a traditional household industry localized in the Khambhat area of Gujarat. The following study analyses the i) age and sex distribution of agate workers ii) factors behind opting for this job and iii) adoption of preventive measures. It was a cross sectional study involving 98 agate workers in Shakarpura engaged in grinding work. The data was analyzed in terms of percentage, mean, S.D, mode, etc. All the agate workers had opted this work because of family constraints. 97(99%) opted this job because of comparative good wages with less hard work than other jobs.15.4% were using the preventive measures. KAP gap of 84.6% was found. It was also revealed that 53.0% were not using the devices because they find it cumbersome to use, difficulty in breathing and because of addiction to various tobacco products.